The Epididymis: Embryology, Structure, Function and Its Role in Fertilization and Infertility - Arrotéia, Kélen Fabiola; Garcia, Patrick Vianna; Barbieri, Mainara Ferreira; Justino, Marilia Lopes; Pereira, Luís Antonio Violin (IntechOpen, 2012)
None